HYPNO-ANDRAGOGY 2.0: TRANSFORMATION OF LEARNING PROCESS USING HYPNOSIS METHOD IN ANDRAGOGY CLASS - Suprijandoko, Firman (PEOPLE: International Journal of Social Sciences, 2018)
It turns out that the technique of teaching in the Andragogy class is very different from the teaching techniques in the Paedagogy class. Note in our previous research there are some trainers who only master substantial competence, but donot master the andragogy. As a result there are trainees who experience the state of Futur while in the classroom. Other significant findings such as in BLC (Building Learning Commitment) classes, where trainees are rather slow in making decisions in the classroom. Their decision-making time below average time. We did research on 6 classes in year 2017. These findings can be solved by the hypno-andragogy method. Hypno-Andragogy is a learning process technique that in delivering the subject matter using communication techniques that are very persuasive and suggestive with the aim that trainees easily understand and feel comfortable in the classroom. In this version 2.0 there is a change in step 4th and 7th. That are Positive vibes with positive self-talk and self-healing using Simple-TRE (Tension and Trauma Releasing Exercise) technique. The use of Hypno-Andragogy methods in the classroom can help create a more effective learning process. Thus, according to the outcomes we expect, the atmosphere in the class becomes more conducive. Class more secure and comfortable. Well motivated trainees. Easy to accept and understand the learning materials so that learning objectives can be achieved.